Cloning and Expression of the Nucleoprotein Gene (NP) of Newcastle Disease Virus (NDV) in Escherichia coli for Immunodiagnosis Application - Silva , Ketherson Rodrigues; Goncalves, Mariana Costa Mello; Oliveira, Elisabete Schirato de; Fernando, Filipe Santos; Montassier, Maria de Fatima Silva; Fernandes, Camila Cesario; Tamanine, Maria de Lourdes Feres; Borzi, Mariana Monezi; Santos, Romeu Moreira dos; Mendonca, Andre de Oliveira; Reischak, Dilmara; Paulillo, Antonio Carlos; et al. (International Journal of Poultry Science, 2014)
The nucleocapsid protein (NP) of newcastle disease virus (NDV) is an important antigen to develop a serologic assay on account of its highly conserved sequences and high immunogenicity. This study aimed to express the gene of the NP of NDV in a heterologous system (Escherichia coli), using the appropriate vector. The NDV-NP protein was expressed as a fusion recombinant protein containing SUMO peptide and poly-histidine tags. This recombinant nucleocapsid protein (rNP) was expressed in a soluble form which was easily purified and showed the ability to react with chicken anti-NDV polyclonal antibodies. An indirect ELISA method based on the adsorption of an antigen composed by NP (rNP-NDV-ELISA) was developed. By comparing this rNP-NDV-ELISA with haemagglutination-inhibition test (HI) high and significant correlation with the HI (r = 0.83) was found. In addition, high sensitivity (88.9%), specificity (95.5%), accuracy (90.4%) and agreement (0.85) were obtained. In conclusion the results indicated that the cloning and expression procedures used in this study provided a rNP that shared the major epitopes with the homologous viral protein and has the potential to be applied in ELISA for the immunodiagnosis of the Newcastle Disease.